Capsaicin and Proton Differently Modulate Activation Kinetics of Mouse Transient Receptor Potential Vanilloid-1 Channel Induced by Depolarization - Takahashi, Kaori; Araki, Kentaro; Miyamoto, Hideo; Shirakawa, Rikimaru; Yoshida, Takashi; Wakamori, Minoru (Frontiers in Pharmacology, 2021)
The transient receptor potential vanilloid type 1 (TRPV1) channel is a non-selective cation channel expressed with TRP ankyrin type 1 (TRPA1) in small and medial size neurons of the dorsal root ganglions and trigeminal ganglions. TRPV1 is activated by capsaicin, thermal stimuli higher than 43°C, mechanical stress, and protons (H+). Although the TRPV1 channel does not have positively charged residues at regular intervals on its transmembrane segments, alterations in membrane potential also affect the state of TRPV1 channel. In the presence of capsaicin, voltage-dependent probability of opening of the TRPV1 channel and its kinetics have been examined, but the characteristics in the low pH remain unclear. To understand the voltage-dependency of the TRPV1 channel activation, we recorded capsaicin- and proton-induced mouse TRPV1 channel currents in a heterologous expression system. Outward current evoked by depolarizing square pulses in the presence of capsaicin or protons was fitted to a two-exponential function with a time-independent component. However, the voltage-dependent changes in amplitude of the three components displayed shallow curves and the changes in their ratio to the total current display similar tendencies in the presence of capsaicin and under the low pH. Fast and slow time constants in the presence of capsaicin were respectively 5- and 8-fold lower than those obtained under low pH conditions. These results suggest that the TRPV1 channel slowly drives the feed-forward cycle of pain sensation, and capsaicin and protons differently modulate the voltage-dependent TRPV1 channel gating.